Grand challenge: social psychology without hubris - Jost, John T. (Frontiers in Social Psychology, 2024)
In this editorial, I take the opportunity to convey some of my own ideas about the past, present, and possible future of social psychology, with the ulterior motive of explaining why I think we will always need social psychology, why we need a new journal in social psychology now, and what kind of journal in social psychology it is I think we need. My history of the field is necessarily brief, highly selective, and admittedly impressionistic, if not downright idiosyncratic. I do not claim that my perspective on the first century and a quarter of social psychology is comprehensive or complete, nor do I expect it to be universally accepted. I am simply offering my take on where we have been, where we went wrong, and where I would like to see us go next.